The complete genome sequence of “Candidatus Liberibacter asiaticus” strain 9PA and the characterization of field strains in the Brazilian citriculture - Michele F. S. Dutra; Priscila A. Silva; Jianchi Chen; Nelson A. Wulff (mSphere)
ABSTRACT “Candidatus Liberibacter asiaticus” (CLas) is associated with citrus huanglongbing, a severe disease with global importance that affects citrus production in Brazil. This study reports the first complete genome of a Brazilian strain of CLas. The genomic structure comparison of strain 9PA with those of 13 complete CLas genomes revealed 9,091 mismatches and 992 gaps/insertions, highlighting eight locally colinear blocks, among which six are in the prophage region. Phylogenetic analysis categorized 13 CLas genomes into two clusters with 9PA clustered with strains from China and the United States. Whole-genomic comparison identified diverse hypervariable genomic regions (HGRs). Three HGRs in the chromosomal region and three in the prophage region were selected and investigated by polymerase chain reaction. HGRs assessed from 68 samples, from medium- to high-huanglongbing incidence areas in Sao Paulo state, were grouped into haplotypes A to P. Haplotype A, which includes strain 9PA, is the second most prevalent, representing 19.1% of the samples. Haplotype B, the most common, accounts for 42.6%. Together with haplotype C, these make up 72% of the evaluated samples. The 9PA strain has prophage P-9PA-1, both integrated and circularized, and P-9PA-3, only found in a circularized form. Prophages show high identity with SC1 (83%) and P-JXGC-3 (98%). Co-occurrence of both type 1 and 3 prophages was observed in field samples. The approach employed provides insights into the Brazilian CLas population, providing markers for population studies and highlighting the prevalence of type 1 and 3 prophages in the population.IMPORTANCECLas is a destructive pathogen responsible for causing the severe citrus disease known as huanglongbing. Our study presents the first fully sequenced Brazilian strain of CLas, designated as 9PA, and includes an analysis of two prophages occurring in this strain. The main objective of our research was to compare the genome features of this Brazilian strain with other fully sequenced genomes and to identify its hypervariable genetic regions. These regions were subsequently used to assess genomic variability within both the chromosomal and prophage regions in Brazilian isolates of CLas. Our findings offer valuable insights into the diversified adaptation of CLas.